Pengaruh Edukasi Kesehatan Tentang Protokol Kesehatan Covid-19 Terhadap Pengetahuan Dan Sikap - Ayu Nurintan; Faisal Kholid Fahdi; Muhammad Ali Maulana (Journal Syifa Sciences and Clinical Research, 2023)
Covid-19 is an infectious disease that affects and infects the respiratory system. From minor respiratory issues like the flu to major ones like pneumonia, lung failure, and even death, Covid-19 can cause a variety of respiratory issues. Close contact and the splash of saliva from an infected individual's talking, coughing, or sneezing can spread Covid-19 from one person to another. Nearly every region of Indonesia has been affected by the Covid-19 illness. To reduce the rate of transmission, the government has set a health protocol policy for daily activities. This can be accomplished by offering health education. Covid-19 and the 5M health regimen, which include utilizing masks, keeping hands, keeping distance, avoiding, and decreasing movement, are two examples of the types of education that can be provided. The purpose of this study was to find out how health education influences changes in students' knowledge and attitudes towards the Covid-19 health protocol. Method: This study is quantitative and uses a pretest-posttest design without a control group as a quasi-experimental approach. With 62 respondents, sequential sampling was the sample technique employed. The Wilcoxon test is the statistical procedure employed. With a significant value of 0.000 (p 0.05) between the pre-test and post-test-1 knowledge variables and a significant value for the pretest attitude variable toward post-test, the results of the various tests using the Wilcoxon test demonstrated that there was a difference in knowledge before and after receiving health education about the Covid-19 protocol. Test-1 is 0.000 (p0.05), indicating that the Covid-19 protocol-related health education had an impact on the attitude variable as well. Conclusion: Students' knowledge and attitudes towards the Covid19 health regimen are influenced by health education.